Autonomic Nervous System Mediates the Hypotensive Effects of Aqueous and Residual Methanolic Extracts of Syzygium polyanthum (Wight) Walp. var. polyanthum Leaves in Anaesthetized Rats. (18th December 2013) - Ismail, A.; Mohamed, M.; Sulaiman, S. A.; Wan Ahmad, W. A. N.
Abstract : Syzygium polyanthum (Wight) Walp. var. polyanthum leaves are consumed as a traditional Malay treatment of hypertension. This study investigates hypotensive potential of aqueous (AESP) and residual methanolic (met-AESP) extracts of S. polyanthum leaves and possible involvement of autonomic receptors. AESP and met-AESP (20 to 100 mg/kg) were intravenously administered into anaesthetized Wistar-Kyoto (WKY) and spontaneously hypertensive (SHR) rats. Blood pressure and heart were monitored for 20 min. AESP and met-AESP induced significant dose-dependent hypotension, but only 100 mg/kg AESP caused mild bradycardia (n = 5 ). AESP-induced hypotension was more potent than that of met-AESP in WKY. AESP has a faster onset time than that of met-AESP in both WKY and SHR. However, met-AESP-induced hypotension was more sustained than that of AESP in SHR. Blockages of autonomic ganglion and α -adrenergic receptors using hexamethonium and phentolamine (n = 5 for each group) partially attenuated AESP-induced hypotension, suggesting involvement of α -adrenergic receptors. Blockages of autonomic ganglion, β -adrenergic, cholinergic receptors, and nitric oxide production using hexamethonium, propranolol, atropine, and N- ω -nitro-l arginine methyl ester (L-NAME) (n = 5 for each group) partially attenuated met-AESP-induced hypotension, suggesting involvement of β -adrenergic and cholinergic receptors via nitric oxide production.